THE IMPACT OF BRAND IMAGE AND SERVICE QUALITY ON BUYING DECISIONS AND ITS IMPLICATION ON CONSUMER SATISFACTION (CASE STUDY AT PT IMI) - Okta Pradita, Sylvia; Arifin Sitio (Dinasti Publisher, 2020)
This study aims to analyze the Impact of Brand Image and Service Quality on Buying Decisions and Its Implications on Consumer Satisfaction (Case Study at PT IMI). This type of research used in this study is a type of causal research with a quantitative approach. The population in this study is all PT IMI customers who have received document storage services as much as 465 customers. The determination of the number of samples was been taken using the Slovin formula to obtain 82 research samples. While analysis technique used is path analysis. The result of these study indicate whether: (1) Brand Image has a positive and significant influence on Purchasing Decisions, (2) Service Quality has a positive and significant effect on Purchasing Decisions, (3) Brand Image has a positive and significant effect on Consumer Satisfaction, (4) Service Quality has a positive effect and significant impact on Consumer Satisfaction, (5) Purchasing Decisions have a positive and significant effect on Consumer Satisfaction.